Unexplored territory in the AFM force curve contains nanomechanics information - Steven J. Eppell; Li Li; Fredy R. Zypman (AIP Advances, 2017)
We demonstrate the existence of a previously unknown damped oscillating signal just after the point when an atomic force microscope tip hits a sample surface. This oscillating signal is below the noise in a single force-displacement measurement. Autocorrelating 20 measurements using the snap to contact feature as the reference mark allows the oscillation to be clearly visible above the noise. We show that the amplitude of the signal’s oscillation is largely insensitive to the speed with which the sample is brought toward the tip proving that the impulse that generates the signal comes primarily from the snap-to-contact event. This speed-independence sets a lower limit on how softly a sample may be interrogated when measuring mechanical properties in the surface region. Collection and analysis of this damped oscillating signal eliminates the need for standard low bandwidth lock-in based techniques to determine time dependent surface mechanical properties. This allows conventional atomic force microscopes to make a single pass of force collection over a surface and, after post-processing, yield the full time dependent mechanical behavior of the surface. To demonstrate a practical use of the oscillations, we produce images of a polystyrene/polyethylene sample where the contrast mechanisms are stiffness and viscosity.